Computer Vision Syndrome: Are Medical Students Exempted from it? -A Cross-sectional Study - Rupali Maheshgaori; Parag Apte; Deepaswi Bhavsar; Gaurav Bramhabhatt; Prachi Bakre (New Frontiers in Medicine and Medical Research Vol. 17, 2021)
Introduction: The usage of computers by medical students has been noted to be on the rise. Computers are employed in many diagnostic examinations that take place within the hospital, and study materials are becoming more digital. The goal of this study was to look into the prevalence, risk factors, and clinical evaluation of computer vision syndrome among medical students, as well as to raise awareness about the condition. Materials and Methods: This cross-sectional investigation was carried out at a Pune medical college. The questionnaire was distributed to students on the medical college’s campus, and those who were determined to be symptomatic were tested further in the Out Patient Department of Ophthalmology, with the data analysed using SPSS software version 17.0. Proportions, percentages, and other applicable statistical methods were used. Statistical significance tests were used. Results: Computer vision syndrome was shown to be prevalent in 54.44 percent of people. Students who use computers for 6-8 hours have a higher percentage (39.12 percent) of computer vision syndrome (CVS), as do students who have used computers for more than 6-8 years. There was statistical significance for both ocular and non-ocular symptoms. Conclusion: Computer vision syndrome was shown to be prevalent in 54.44 percent of medical students. Factors that alleviate symptoms were also investigated, and it was discovered that being aware of CVS significantly reduces symptoms.